2021
DOI: 10.1016/s2352-3026(21)00169-1
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of the BNT162b2 COVID-19 mRNA vaccine and early clinical outcomes in patients with haematological malignancies in Lithuania: a national prospective cohort study

Abstract: Background Haematological malignancies and their treatments are likely to affect SARS-CoV-2 vaccine efficacy. We aimed to evaluate serological response to BNT162b2 vaccine in patients with haematological malignancies by type of treatment. Methods Our national prospective cohort study was done in Lithuania and assessed serological response to one and two BNT162b2 (Comirnaty, Pfizer-BioNTech) vaccine doses in healthy health-care workers and in patients with haematological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
296
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(343 citation statements)
references
References 24 publications
(27 reference statements)
27
296
2
Order By: Relevance
“…Our results are consistent with those reported for immunosuppressed populations such as patients with chronic lymphocytic leukemia [14], and organ transplant recipients [32]. Immunosuppression has been shown to decrease the immune response in other vaccine studies, and particularly in patients with hematological malignancies who developed severely diminished antibody responses compared with healthy individuals [14][15][16]. These populations are at increased risk of SARS-CoV-2 infection despite vaccination.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results are consistent with those reported for immunosuppressed populations such as patients with chronic lymphocytic leukemia [14], and organ transplant recipients [32]. Immunosuppression has been shown to decrease the immune response in other vaccine studies, and particularly in patients with hematological malignancies who developed severely diminished antibody responses compared with healthy individuals [14][15][16]. These populations are at increased risk of SARS-CoV-2 infection despite vaccination.…”
Section: Discussionsupporting
confidence: 90%
“…The Centers for Disease Control and Prevention (CDC) recommends that vaccination be delivered 2 weeks prior to immunosuppressive therapy [12], but this is not possible in patients already on chemotherapy [12,13]. Several new studies raised concerns about the blunted antibody responses to the COVID-19 vaccine in patients with hematological malignancies [14][15][16]. A recent study reported that the BNT162b2 vaccine does have an acceptable short-term safety profile in patients treated with immune checkpoint inhibitors [17], but data on the efficacy of the vaccine in cancer patients with solid malignancies treated with anti-neoplastic drugs are scarce [18,19].…”
Section: Introductionmentioning
confidence: 99%
“… 1 Similarly, in one large study of 885 patients with haematological malignancies, including patients who had and had not undergone transplantation, the treatments actively received at time of vaccination were the primary determinants of the antibody response. 9 Nine cases of breakthrough severe SARS-CoV-2 infections were reported in this previous study, which we did not observe in the present study, occurring in fully vaccinated patients who had mostly low anti-S-RBD IgG antibody titres.…”
contrasting
confidence: 74%
“…Our report adds to the results of a series of studies that have investigated humoral and cellular responses to SARS-CoV-2 vaccination in patients with a history of B-cell depleting anti-CD20 therapies. 11 , 12 , 16 , 28 , 29 , 30 , 31 Deepak and colleagues 11 first reported a 36-fold decrease in vaccine-induced anti-spike IgG titres in patients with B-cell depleting therapies. Simon and colleagues 30 and Apostolidis and colleagues 29 reported no detectable or severely diminished vaccine-induced humoral immune responses compared with controls in two smaller series of patients with severely depleted B-cell counts, but both studies reported detectable cell-mediated immunity in these patients.…”
Section: Discussionmentioning
confidence: 99%